The Introduction of Calculation at The Preparatory Center in Islamic Kindergarten Nibras Padang - Wulansari Vitaloka (Universitas Muhammadiyah Mataram, 2018)
The problem in this research is the center approach as a learning model is still not used in KINDERGARTEN. Because teachers have not understood the center approach and the introduction of counting in children is not optimal, it is difficult for teachers to determine the right method. The purpose of this research is to describe the methods used by teachers in the identification of calculation at the preparatory center at the Islamic kindergarten Nibras Padang. The research methods used in this study are descriptive with a qualitative approach. The informant in this study was the teacher at the center of preparation as well as the principal. The results of this research can be concluded that the method used in the introduction of calculation of the preparation center in TK Nibras Islam is at the reception of the teacher's child using the question and answer method, on the footing before playing the teacher using methods of play, methods of giving assignments and methods of demonstration, on footing during the main teacher using methods of play, question and answer methods, demonstration methods, experimental methods and methods of dramatization, on the footing after playing the teacher using methods of play, question and answer methods, and methods of storytelling.